The Potentials of Tourism Industry in Uzbekistan and Effective Use of Them for Sustainable Development - Ergashev Ramziddin Fakriddinovich (Universitas Muhammadiyah Sidoarjo, 2020)
Tourism is one of the most growing industries that it contributes to the development of most countries especially, developing ones. It creates a huge number of jobs, improves the lifestyle of people and boosts the economy of the country. Uzbekistan has its own potentials in the sphere of tourism mostly connected with culture, history, religion, and traditions, and the government is also paying much attention to the development of the tourism sector. The article examines the problems in tourism sphere that Uzbekistan has to tackle and suggests solutions to them. It also gives information about the potentials that the country has including climate, nature, exotic landscapes, culture, mountains and foods and steps that should be taken in order to use them effectively which guarantee sustainable development. One of the most important steps is to use the most recent technologies and innovations to improve tourism and make it much more comfortable for tourists. Making services available online and teaching qualified and competitive staff are also considered as crucial steps. All products and all the services should be interconnected with each other. Reducing unnecessary limitations for travel agencies, hotels or entertaining places would also contribute to the development of the hospitality business. Increasing the contribution of the tourism industry to our GDP should be our main goal since its contribution is less than 3% while in most countries it accounts for 10-45%. The main type of tourism in Uzbekistan is cultural tourism since it has more than 7300 cultural heritages and over 200 of them are listed among UNESCO World Heritage Sites. Samarkand, Bukhara, and Toshkent are the best places to improve Ziyarat Tourism. Another most important point would be focusing on the promotion and changing the people’s opinions about Uzbekistan which are often negative.